O estado da ciência, tecnologia e inovação e sua relação social com enfermagem no Brasil - Binotto, Cibele Correia Semeão (2012)
In Brazil, there are few studies that search to know how health professionals to access, retrieve, understand, assimilate and utilize the scientific and technological information available. If this studies are contributing to improvement the management of health care such as increasing in researchs and development, it can not be to accompanied by society, which seems to demonstrate that there are not connection between research sector and industry. The research aims to investigate and categorize how to configurate the scientific production of nursing science and its relationship with the social priorities in health research. It is an exploratory research with construction of referential and reflections theoreticals about science national policy, technology and innovation in health, nursing research in health public in Brazil; science, technology and society for the evaluation of scientific and technological activities and automated tools for data quantitative analysis. After selection of nursing journals in the SCIELO, we are searching for health articles, through terms present in the descriptors on scientific basis and then to use in bibliometric studies. In this research was possible to verify coherence between electronic library of SCIELO and descriptors system of BIREME showing a work jointly. Of studied articles was possible to identify compliance with health policies and some its themes, evidencing others themes that are not well explored yet. This research is coming contributing to the characterization of current scientific production in health, encouraging researchers to know the profile of publications, the most exploited themes, possible gaps and its colaborators. The use of electronics journals makes easily access and it contribute to new researchs, is becoming much easier located through keywords leads to a quick reference. So information technology is highlighted as way that decreasing the gap between researchers and scholars.